The Quality of Counseling for Headache OTC Medications in German Community Pharmacies Using a Simulated Patient Approach: Are There Differences between Self-Purchase and Purchase for a Third Party? - Bernhard Langer; Christian Kunow (The Scientific World Journal)
Background. In Germany—as worldwide—headache is one of the most frequent causes of self-medication. The dispensing of over-the-counter (OTC) medications may only be carried out by community pharmacies (CPs). In doing so, CPs have to ensure “adequate” counseling, for both self-purchase and purchase for a third party, which also occurs in everyday pharmacy practice. The aim of this study was to evaluate the quality of counseling for headache OTC medications in German CPs and, as the first study worldwide, to analyze whether and to what extent there are differences in counseling between self-purchase and purchase for a third party. Methods. A cross-sectional study was carried out using the covert simulated patient methodology (SPM) in all 42 CPs in the German big city Potsdam. With the help of 8 trained simulated patients (SPs), each CP was visited four times by a different SP. The SPs simulated in each CP two scenarios two times with the demand for an OTC medication against headache, which differed only in whether the demand was for themselves or for their boyfriend/girlfriend. Results. All 168 planned pharmacy visits (84 visits per scenario) were successfully carried out. Overall, the median counseling score was 3.0 out of 9 points (interquartile range [IQR 2.0]). There were no significant differences between the two scenarios (Wilcoxon signed-rank test; p=0.495, r = 0.053). In a multivariate binary logistic regression analysis, the counseling level and the different scenarios were not significantly associated (adjusted odds ratio [AOR] = 1.635, 95% CI = 0.673–3.972, p=0.278). Conclusions. Due to the partly considerable deficits in counseling of German CPs, policy-makers and the regional chambers of pharmacists are called upon to take appropriate measures to improve the quality of counseling. It is positive that no differences in counseling between self-purchase and purchase for a third party were found, but further verifying studies with a modified methodology are recommended.